Case report on transitional cell carcinoma of male urethra - Rahman, S; Regmi, S; Zaman, M; Islam, S; Ullah, A T M A; Islam, M S; Hossain, K M; Salam, M A (Bangladesh Journal of Urology, 2012)
No abstract available. BJU 2010; 13(1): 38-41